Catechol-O-Methyltransferase Polymorphism Influences Outcome After Ischemic Stroke: A Prospective Double-Blind Study. (July 2013) - Liepert, Joachim; Heller, Andreas; Behnisch, Gusalija; Schoenfeld, Ariel
Background . To explore whether a polymorphism in dopamine metabolism influences the effectiveness of neurological rehabilitation and the outcome after ischemic stroke. Methods . The Barthel Index (BI) and the Rivermead Motor Assessment (RMA) were assessed in 78 moderately affected stroke patients (1) after they had entered a neurological inpatient rehabilitation, (2) after 4 weeks of rehabilitation therapy, and (3) 6 months later. Polymorphisms of the gene encoding catechol- O -methyltransferase (COMT) were determined. BI and RMA results were analyzed with respect to the genetic profiles of COMT. Results . Carriers of COMT Val/Val alleles showed better results in BI and RMA than COMT Met/Met carriers at all 3 time points. Val/Met carriers exhibited results in between the homozygotes, suggesting a gene–dose relationship. Altogether, BI and RMA results were highly correlated. Conclusion . Stroke patients with COMT Val/Val alleles had higher motor functions and abilities of activities of daily living even at the beginning of the rehabilitation period. All patient groups improved during the rehabilitation period to a similar degree, suggesting that physical therapy is comparably effective in all polymorphism subtypes.